Removal, Resistance and Stay of the Slum (favela) on the brazilian urban board: The Public Housing Program Morar Feliz, in Campos dos Goytacazes-RJ - Peixoto Faria, Teresa de Jesus; Ribeiro de Oliveira Pohlman, Maria Alice (Geografares, 2017)
The present article discuss the practice of removal procedures related to the implement of the Public Housing Programs and urban renewal, in Brazil, and its social and spatial impacts, in particular the Morar Feliz Program, from Prefeitura Municipal de Campos dos Goytacazes. We study the process of removal on Goiabal “slum”, considered as a risk area, because is seated on the shore of Paraíba do Sul river. The most of the buildings was demolished and its habitants were removed to the Public Housing Morar Feliz in the Novo Jockey district. Some families resisted and keep on living at the place, justifying addiction to the place, relation with the river – many of them are fishermen – proximity to the family and to the job. We consider that the resistance movements can be inserted on the slums general historie, that being results of the segregating and inequal urbanization process, belongs to the landscape of almost all brazilian cities. This article discuss the Morar Feliz Program and the resistance movements on Goiabal “slum” from the report of those that experienced the removal and resisted to it, emphasizing their strategies of appropriation and uses of the space – both physical and social – and their reflections on Group Identity Affirmation and of the place where they live and, by consequence, of the city.Keywords: Slum, Housing Policy, removal, sociospatial injustice.